Association between high-risk pregnancy and mode of delivery in Kalibaru - Aslina, Wiwit; Silviatul Amalia; Nita Indah Lestari (Journal of Health Technology Assessment in Midwifery, 2025)
High-risk pregnancy is a critical public health concern associated with increased maternal and neonatal morbidity and mortality, particularly in developing regions such as Banyuwangi, Indonesia. The Kalibaru area reported the highest number of pregnant women with complications in 2024. This study aims to examine the relationship between high-risk pregnancy status and mode of delivery in Kalibaru, addressing a gap in literature regarding their association. A retrospective cross-sectional study was conducted using secondary data from 762 postpartum mothers in Kalibaru. A total of 262 samples were selected using Slovin’s formula with a 5% margin of error and simple random sampling. Eligibility criteria included complete medical records from women who delivered in Kalibaru in 2024. Data were anonymized and analyzed using the Chi-Square test to determine the association between high-risk pregnancy status (categorized as high-risk or not) and delivery method (vaginal or cesarean section).Among the 262 respondents, 198 (75.6%) had high-risk pregnancies and delivered via cesarean section (CS), while 64 (24.4%) had spontaneous vaginal births. The Chi-Square test showed a statistically significant association between high-risk pregnancy and cesarean delivery (p = 0.000). Odds ratio analysis revealed that high-risk pregnant women were 63.68 times more likely to undergo cesarean section (OR = 63.677; 95% CI: 9.108–445.161) compared to non-high-risk women. Key risk factors contributing to the increased likelihood of cesarean delivery included maternal age <20 or >35 years, height ≤145 cm, low parity, and prior cesarean history. These findings highlight the importance of early detection and comprehensive risk assessment during antenatal care to reduce medically unnecessary cesarean sections. Implementation of routine pregnancy risk screening using tools such as the Poedji Rochyati Scorecard (KSPR), along with strengthening referral systems and public education, is essential for improving maternal outcomes in high-risk pregnancies.